2017
DOI: 10.1177/0047239517736873
|View full text |Cite
|
Sign up to set email alerts
|

Education Student Perceptions of Virtual Reality as a Learning Tool

Abstract: The purpose of this study was to ascertain student perceptions of the use and value of three-dimensional virtual environments. A grounded theory approach was used to gather and examine data. Just over half of student participants reported positive experiences. However, most experienced technical difficulties. Despite the technical challenges of operating within the virtual space, the majority reported positive aspects of using the virtual space, including increased meaningful social interactions and reduced so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 11 publications
1
38
0
4
Order By: Relevance
“…Currently, prices of viewers are excessively high in order to use them in the classroom in all their potential, so their use is very reduced and limited.Concerning the current use of virtual reality as a learning tool, it is still a minority who uses it for this purpose (13.7% of the sample). However, this fact is not yet alarming, because we are facing a technology that takes its first steps, with numerous lacks, especially regarding everything that goes beyond the leisure field (Domingo and Gates Bradley, 2017). Those who use virtual reality as a learning tool (13.7%) are usually women, show more interest in learning with virtual reality and would like to learn in the future in formal education using this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, prices of viewers are excessively high in order to use them in the classroom in all their potential, so their use is very reduced and limited.Concerning the current use of virtual reality as a learning tool, it is still a minority who uses it for this purpose (13.7% of the sample). However, this fact is not yet alarming, because we are facing a technology that takes its first steps, with numerous lacks, especially regarding everything that goes beyond the leisure field (Domingo and Gates Bradley, 2017). Those who use virtual reality as a learning tool (13.7%) are usually women, show more interest in learning with virtual reality and would like to learn in the future in formal education using this technology.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this research is to analyze the potential impact of using virtual educational tools would have on a technical university, as perceived by the students and professors that attend that university. There are other authors that have conducted research in this field and have found contradicting results in regards to how students and teachers perceive this kind of technology [4] [5], in regards to the effect that using this kind of technology has on their performance. Other authors have experimented with using virtual technologies in other fields, such as medical ones [6], and have noticed that students have a better understanding of how technical procedures function and an improvement in surgical procedures [7] overall.…”
Section: Literature Reviewmentioning
confidence: 96%
“…3D-VLE merupakan salah satu jenis e-learning yang mengintegrasikan teknologi informasi dan komunikasi dalam proses pembelajaran , (Simonics, 2013). Sistem 3D-VLE juga merupakan platform yang dapat dikembangkan berdasarkan imajinasi dari penggunanya (Reisoğlu, et al, 2017) dan pada umumnya dikenal juga sebagai course management system yang dapat divisualisasikan dalam bentuk lingkungan 3 dimensi, serta banyak digunakan pada proses pembelajaran pembelajaran (Livingstone & Kemp, 2008), (Chau, et al, 2013), (Ak & Kutlu, 2015) untuk meningkatkan keterlibatan dan pengalaman belajar peserta didik (Domingo & Badley, 2018), (Karaman & Özen, 2016).…”
Section: Pendahuluanunclassified